2019
DOI: 10.1021/acs.est.9b06051
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Major Contributions of Unintentionally Produced PCBs in the Air of China: Implications for the National Source Inventory

Abstract: Polychlorinated biphenyls (PCBs) were not widely manufactured or used in China before they became the subject of international bans on production. Recent work has shown they have reached China associated with imported wastes, and that there are considerable unintentional sources of PCBs that have only recently been identified. As such, it was hypothesised that the source inventory and profile of PCBs may be different or unique in China, compared to countries where they were widely used and which have been wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 66 publications
1
48
0
Order By: Relevance
“…Both parent PCB 11 and its hydroxylated, glucuronidated, and sulfated metabolites have been detected in blood samples of exposed individuals (Grimm et al 2017;Sethi et al 2017Sethi et al , 2019Zhu et al 2013). Nonlegacy PCBs, also called unintentionally produced PCBs, now represent the major source of PCBs in the atmosphere of China (Zhao et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both parent PCB 11 and its hydroxylated, glucuronidated, and sulfated metabolites have been detected in blood samples of exposed individuals (Grimm et al 2017;Sethi et al 2017Sethi et al , 2019Zhu et al 2013). Nonlegacy PCBs, also called unintentionally produced PCBs, now represent the major source of PCBs in the atmosphere of China (Zhao et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2013 ). Nonlegacy PCBs, also called unintentionally produced PCBs, now represent the major source of PCBs in the atmosphere of China ( Zhao et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the online tool to estimate R values reduces sample processing steps and eliminates the high costs associated with isotopically labeled chemical standards. The model has been used and validated in other passive air sampling campaigns by Zhao et al 2020 25 and Bohlin-Nizzetto et al 2020. 26 Concentrations in air reported in this study are estimated from modeled R values (data reported in previous studies for the years 2005–2009 were corrected based on the new R values).…”
Section: Experimental (Materials and Methods)mentioning
confidence: 99%
“…This is of particular concern should the unknown transformation products be more hazardous than their precursor species, thus making an accurate risk assessment of CECs unattainable.The lack of transformation product identi cation and information associated with their PBT is in part, due to the current target-analysis approach to identifying harmful airborne CECs. 13,14 It is also a result of the immense analytical challenge associated with tracking complex mixtures of airborne chemicals. 7 In particular, atmospheric transformation products, for which no analytical standards exist, are very di cult to distinguish from other species present in complex mixtures.…”
mentioning
confidence: 99%
“…However, CEC transformation products formed in air are not measured in current international and national atmospheric monitoring networks despite their intent of tracking global and regional distributions of CECs. [13][14][15] As a result, only a fraction of the CEC-related chemicals which exist have been monitored. This is of particular concern should the unknown transformation products be more hazardous than their precursor species, thus making an accurate risk assessment of CECs unattainable.The lack of transformation product identi cation and information associated with their PBT is in part, due to the current target-analysis approach to identifying harmful airborne CECs.…”
mentioning
confidence: 99%